SYNTHETIC FLUID INCLUSIONS: XVI. PVTX PROPERTIES IN THE SYSTEM H2O-NACL-CO2 AT ELEVATED TEMPERATURES, PRESSURES, AND SALINITES - Schmidt C.; Bodnar R.J. (My University, 2000)
The ternary system H2O-NaCl-CO2 is one of the most important fluid systems in geochemistry and petrology. However, there is little information on the phase equilibrium and PVT properties in this system at salinities above 6 wt.% NaCl. In this study, PVTX data were obtained experimentally by using the synthetic fluid inclusion technique in conjunction with conventional microthermometry and a hydrothermal diamond–anvil cell.Solvi (liquid-vapor boundaries) and lines of equal homogenization temperature (approximating lines of constant density) were determined for pressures between about 100 and 500 MPa, temperatures of 300°C to 800°C, and compositions up to 40 wt.% NaCl and 20 mol.% CO2, both relative to water. Critical temperatures were obtained for ternary compositions ≤ 20 wt.% NaCl and ≤ 20 mol.% CO2, both relative to water.For a constant homogenization temperature, the dP/dT slopes of lines of equal homogenization temperature become steeper along pseudobinaries with both increasing carbon dioxide concentration and increasing NaCl. At constant salinity, the high-pressure portion of the solvus shifts to higher pressures and temperatures with increasing CO2 concentration. Addition of carbon dioxide causes the critical point to migrate towards higher pressures and slightly lower temperatures. For concentrations less than 20 wt.% NaCl and less than 20 mol.% CO2, the main effect of an increase in salinity at a fixed H2O/CO2 ratio is a sharp rise in the critical temperature, coupled with a moderate shift of the critical point towards higher pressures. The addition of CO2 and NaCl causes the solvus to migrate to high temperatures and pressures, reaching granulite–facies conditions for moderate to high concentrations of CO2 and NaCl. The results of this study are combined with literature data to construct P-T sections, with lines of constant homogenization temperature, for various compositions in the H2O-NaCl-CO2 ternary, and the results are compared with results predicted by a recently published equation of state.